Quality of life as the basis for achieving social welfare of the population; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Krinitsyna Z. V. Zoya Vasilievna (2016, 2016)
Title screen